Banking Share Prices Analysis: The Influence of Financial Ratios Amidst Digital Transformation - Purwanto, Setiyo; Perkasa, Didin Hikmah (Quantitative Economics and Management Studies, 2024)
This research aims to analyze the influence of financial ratios on share prices in the banking sub-sector listed on the Indonesia Stock Exchange. The approach in this research is to use a quantitative approach and based on its objectives, this type of research is causal, namely research that explains the influence of an independent variable on the dependent variable. The independent variables in this research include Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Assets (ROA) and the dependent variable in this research is Stock Price. The population of this research is banking companies listed on the Indonesia Stock Exchange, totaling 46 banking issuers. The sample determination procedure uses a non-probability sampling method, namely in the form of purposive sampling. Purposive sampling is a sampling technique with certain considerations. Based on the selection results, there were 20 banks that met the criteria. Data analysis was carried out using multiple linear regression analysis. The results of the analysis show that the Current Ratio and Debt to Equity Ratio have a negative effect on stock prices, Return On Assets have a positive effect on share prices.